Shen Shuai II Recipe alleviates renal fibrosis in chronic kidney disease by improving of hypoxia and inhibition of TLR4/MyD88/NF-κB/NLRP3 pathway - Yuan Zhou; Liang Zhou; Meng Wang; Lin Xu; Tingting Li; Chen Wang (Renal Failure)
Objectives To investigate the anti-fibrotic mechanisms of Shen Shuai II Recipe (SSR) in chronic kidney disease (CKD), focusing on its modulation of hypoxia-associated inflammatory pathways and the TLR4/MyD88/NF-κB/NLRP3 axisMethods A 5/6 nephrectomy-induced chronic renal failure (CRF) rat model and hypoxia-exposed human renal tubular epithelial (HK-2) cells were utilized. In vivo, renal function was assessed via serum creatinine, urea nitrogen, and creatinine clearance measurements, alongside histopathological evaluation of renal fibrosis and inflammation. In vitro, hypoxia-treated HK-2 cells were analyzed for fibrotic markers (fibronectin, collagen I, α-smooth muscle actin) and pro-inflammatory cytokines (IL-1β, IL-18). Molecular mechanisms were probed through protein expression analysis of HIF-1α and the TLR4/MyD88/NF-κB pathway, with NLRP3 inflammasome activity evaluated.Results SSR treatment significantly improved renal function in CRF rats, reducing serum creatinine (Scr) and urea nitrogen (BUN) while enhancing creatinine clearance. Histopathology revealed preserved renal architecture with attenuated fibrosis and inflammatory infiltration. In hypoxic HK-2 cells, SSR downregulated fibrotic markers and suppressed IL-1β and IL-18 levels. Mechanistically, SSR reduced HIF-1α expression, inhibited TLR4/MyD88/NF-κB signaling, and suppressed NLRP3 inflammasome activation in both models.Conclusions SSR alleviates renal fibrosis and CKD progression by mitigating hypoxia-driven inflammation and blocking the TLR4/MyD88/NF-κB/NLRP3 pathway.